2002
DOI: 10.1002/ana.10440
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine, white matter hyperintensities, and cognition in healthy elderly people

Abstract: Hyperhomocysteinemia is associated with an increased risk of vascular disease, and recent results suggest that it also could increase the risk of dementia. We examined the relationship between homocysteine and cognitive decline in 1,241 subjects aged 61 to 73 years, followed up over 4 years. Plasma homocysteine levels were determined in all participants as well as cardiovascular risk factors, apolipoprotein E genotype, plasma levels of folate, and vitamin B12. Cognitive performances were assessed repeatedly by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
157
3
2

Year Published

2004
2004
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(175 citation statements)
references
References 53 publications
(48 reference statements)
13
157
3
2
Order By: Relevance
“…Serum methylmalonic acid (390 Ϯ 390 nmol/L) and homocysteine (16.5 Ϯ 6.2 mol/L) concentrations in the United Kingdom were also higher than those observed for our CHAP subjects. In a representative postfortification US sample of older adults, homocysteine levels ranged from 8 to 10.7 mol/L 31 ; in two prospective studies of older adults, 28,33 values were similar to those reported in the present study, which spans a pre-to perifortification period.…”
Section: Resultssupporting
confidence: 85%
“…Serum methylmalonic acid (390 Ϯ 390 nmol/L) and homocysteine (16.5 Ϯ 6.2 mol/L) concentrations in the United Kingdom were also higher than those observed for our CHAP subjects. In a representative postfortification US sample of older adults, homocysteine levels ranged from 8 to 10.7 mol/L 31 ; in two prospective studies of older adults, 28,33 values were similar to those reported in the present study, which spans a pre-to perifortification period.…”
Section: Resultssupporting
confidence: 85%
“…Moreover, the fi gures reported above do not necessarily take into account the infl uence of risk factors for stroke and concomitant vascular disease. Given that newer research suggests that risk factors for stroke are also risk factors for AD (Dufouil, Alperovitch, Ducros, & Tzourio, 2003 ;Fernando & Ince, 2004 ;Riekse et al, 2004 ;Szolnoki et al, 2004 ), the fi gures reported above may be underestimating the prevalence of dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Some have shown significant associations between homocysteine levels and cognitive function, 10,[12][13][14][15][16][17][19][20][21][22] whereas others have not. 11,18 An early study involving a small sample of a healthy elderly population in Italy showed no significant correlations between the Mini-Mental State Exam (MMSE) scores and homocysteine levels.…”
Section: Homocysteine and Cognitive Function Scoresmentioning
confidence: 99%